Titularidade municipal da drenagem e manejo das águas pluviais em municípios de pequeno porte populacional e impactos na saúde : o caso das arboviroses - Marco Túlio da Silva Faria (2023)
In Brazil, basic sanitation is a municipal right and for the exercise of this right and duty of the state, it is essential that municipalities structure their municipal policy, with planning being its main instrument and challenge. Given this scenario, we sought to analyze the Drainage and Stormwater Management (DSM) and its relationship with the monitoring and control of the Aedes mosquito within the municipal sanitation policy. A systematic review was conducted to identify studies on this theme in the literature. An overview of the existence of Municipal Sanitation Plans (PMSB) and Urban Drainage Master Plans (PDDU) in municipalities with populations of less than 50 thousand inhabitants in the state of Minas Gerais was prepared. Subsequently, content analysis was performed on 16 PMSB to evaluate the approach to DMAP and arboviroses in the plans. Finally, a content analysis was performed in guiding instruments of public policies in the context of confronting arboviroses in Brazil to analyze how the integration of sanitation and health are addressed. Twenty-one articles were identified whose main theme is the DSM and the proliferation of mosquitoes of the genus Aedes. Among the 752 small-sized municipalities in the state of Minas Gerais, 499 of them have PMSB, while none of them has PDDU. With regard to the content analysis of the 16 PMSB, the results show the precariousness of the management of DMAP services in the municipalities under study, highlighting the absence of DMAP devices, registration of systems, frequent maintenance and cleaning, municipal financial resources for investments and qualified professionals. The arboviroses and other Diseases Related to Inadequate Environmental Sanitation (DRSAI) are present in the PMSB and are directly related to inadequate access to sanitation services. However, the proposed actions to control these diseases consist mostly and formally in processes of education and awareness of the population. The search for intersectoriality and integrality in the provision of sanitation services is recognized as essential in the PMSB, although its reach in practice is limited. Therefore, the results generated here can help in future public policies aimed at monitoring and controlling the Aedes mosquito, besides highlighting the importance of the component Drainage and Stormwater Management in this context. After the analysis of how sanitation is approached in guiding instruments of public policies in the context of confronting urban arboviroses in Brazil, it is clear that this theme is little addressed and the actions are not clearly presented in the documents that deal with the subject.